If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(7x+5)+20=2(3x-1)
We move all terms to the left:
2(7x+5)+20-(2(3x-1))=0
We multiply parentheses
14x-(2(3x-1))+10+20=0
We calculate terms in parentheses: -(2(3x-1)), so:We add all the numbers together, and all the variables
2(3x-1)
We multiply parentheses
6x-2
Back to the equation:
-(6x-2)
14x-(6x-2)+30=0
We get rid of parentheses
14x-6x+2+30=0
We add all the numbers together, and all the variables
8x+32=0
We move all terms containing x to the left, all other terms to the right
8x=-32
x=-32/8
x=-4
| k+4(-6k+1)=-5-7(1+k) | | 2r+7=-9−6r | | 4(y+12)=48 | | 9+2h=-h | | x/4-13=19 | | 7(1-2x)-3=4-21x | | 2=p−32 | | 23–4u=11 | | 35=2w+15 | | 11+23+x+19-x=50 | | 18=w/2-9 | | X+6+12+2x=54 | | x+31/7=4 | | 4=21x-18 | | 7n+33=-23 | | -3x+32+5x=-422x+8=−10 | | t/3-20=70 | | 166=3n+4 | | 3/4=w/10 | | 2(-x-4)=-2x+6 | | 100=3n+4 | | 2(3r+4)-3(r+1)=26 | | 4v+15=17 | | 61=3n+4 | | -3/8x+8=-31 | | 8r-4=-6r+-32 | | 11+23+x19-x=50 | | 88=-4(7x+6) | | -2(2k-5)=34 | | 5t−11=2 | | -19y-3y+8=-14 | | 8z+5=7z+2 |